Upaya Pencegahan Penyakit Kulit pada Kelompok Pemulung di Tempat Pembuangan Akhir (TPA) Suwung, Bali - Pande Ayu Naya Kasih Permatananda; Luh Gde Evayanti; I Gede Suranaya Pandit (Universitas Katolik Widya Karya Malang, 2023)
Suwung Garbage Landfill is the largest landfill in Bali with a land area of 32.48 hectares. Scavengers are a profession that is prone to skin diseases. Previous observational studies concluded that most of scavengers at the landfill had complaints of skin disease which might be caused by the scavengers’ low knowledge of personal hygiene. This community service was carried out in January-February 2023, starting with interview and dialogue with the Suwung Landfill manager, transfer the science and technology, and evaluate the activities. The activities carried out included: counselling on skin diseases and their prevention, socialization of personal protective equipment (PPE), demonstration and exercise 7 steps of hand washing, and providing personal hygiene and PPE assistance. The entire series of activities was attended by 20 scavengers with active participation. The results of posttest using 10 multiple choice questions showed that all participants were able to score more than 70. Through this community service, it is hoped that scavengers will be able to increase their awareness regarding of skin disease and be able to take appropriate precautions